Development of Student Worksheets Based on Problem Based Learning (PBL) Assisted by PhET Simulations to Improve Mastery of High School Physics Concepts - Maulana, Lalu Muhammad Septian; Kosim, Kosim; Zuhdi, Muhammad; Wahyudi, Wahyudi (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
This development research aims to produce a product in the form of a Student Workshees (known LKPD) based on a problem-based learning model that is feasible, practical and effective for improving students' mastery of concepts. This research is included in Research and Development (R&D) with a 4D model, which consists of defining, designing, developing, and disseminating. The product developed is Newton's Law LKPD supported by other independent curriculum tools: Learning Outcomes, Learning Goal Flow, Teaching Modules, and concept mastery test instruments. Data collection techniques use validation sheets, learning implementation observation sheets, student response questionnaires, and test instruments. The validity of the product was assessed by three expert validators, who were physics lecturers, and three practitioner validators, who were physics subject teachers. Their evaluations were performed using a Likert scale. Practicality is obtained from the teacher's observation sheet and student response questionnaires regarding learning. Effectiveness was obtained from the results of limited product trials in the form of an increase in pretest and posttest scores, which were analyzed using the n-gain test. The results of the validity of the product developed have a percentage, namely LKPD 92.12%; Learning Achievement 92.08%; Flow of Learning Objectives 92.60%; Teaching modules 89.78% and test instruments 91.15% with very valid and reliable categories above 75%, so the product can be said to be suitable for use. The results of the product's practicality were in the form of an implementation sheet by the teacher. Student responses of 92.08% and 82.10% were written in the convenient category. The results of the n-gain test for students' concept mastery were 0.74 in the medium category and included in the very effective criteria. Thus, the LKPD, Learning Outcomes, Learning Goal Flow, Teaching Modules and test instruments produced are feasible, practical and effective in improving students' mastery of concepts.